Preprocedure and Postprocedure Predictive Values of Serum β2-Microglobulin for Contrast-Induced Nephropathy in Patients Undergoing Coronary Computed Tomography Angiography: A Comparison With Creatinine-Based Parameters and Cystatin C. Issue 6 (November 2015) - Li, Suhua; Zheng, Zhenda; Tang, Xixiang; Peng, Long; Luo, Yanting; Dong, Ruimin; Zhao, Yunyue; Liu, Jinlai
Abstract : Objective: This study aimed to investigate the values of serum β2-microglobulin to predict contrast-induced nephropathy (CIN) before and early after coronary computed tomography angiography (CCTA), comparing with creatinine-based parameters and cystatin C. Methods: A total of 424 patients were enrolled. Serum β2-microglobulin, cystatin C, and creatinine were measured at 0, 24, and 48 hours of CCTA. Contrast-induced nephropathy was defined as an elevation of serum creatinine level by 25% or higher or 0.5 mg/dL or greater from baseline within 48 hours. The estimated glomerular filtration rate (eGFR) was calculated by the Modification of Diet in Renal Disease study equation. Receiver operating characteristic curves and multivariate logistic regression analysis were used to detect the efficiency of biomarkers in predicting CIN. Results: Fifty-two subjects (12.26%) developed CIN. Before CCTA, CIN was predicted by both baseline β2-microglobulin (area under the receiver operating characteristic curve [AUC], 0.791; P < 0.001) and cystatin C (AUC, 0.781; P < 0.001), whereas creatinine and eGFR were not predictive. After CCTA, CIN was predicted by both the absolute post-CCTA levels of β2-microglobulin, cystatin C, creatinine, and eGFR (AUC, 0.842 vs 0.961 vs 0.691 vs 0.688 at 24 hours, P < 0.001; and 0.937 vs 1.000 vs 0.908 vs 0.898 at 48 hours, P < 0.001) and their relative changes (Δ) to baseline (AUC, 0.677 vs 0.846 vs 0.850 vs 0.844 at 24 hours, P < 0.001; and 0.731 vs 0.968 vs 0.984 vs 0.966 at 48 hours, P < 0.001). Multivariate regression analysis confirmed that baseline β2-microglobulin (odds ratio, 2.137; 95% confidence interval, 1.805–3.109; P < 0.001) and cystatin C (odds ratio, 1.873; 95% confidence interval, 1.667–2.341; P = 0.003) were independent predictors for CIN. Conclusions: Serum β2-microglobulin, with values superior to creatinine-based parameters and similar with cystatin C, was a useful biomarker for the prediction of CIN at pre-CCTA and early post-CCTA.